(untitled) (The Chittagong University Journal of Science, 2023)
This study examines the impact of selected socio-economic and demographic factors on divorced in Chattogram Metropolitan Area (urban area) and rural areas of Chattogram district, Bangladesh. In both the areas, logistic regression analysis reveals that occupation of respondents (women) and husbands, respondent’s age, drug addiction status of husbands, respondent’s educational qualifications, dowry taken by husbands, use of mobile phone or Facebook etc. are the positively significant effects on divorce. The Chittagong Univ. J. Sci. 44(1): 17-32, 2022